Is What is Good for the Goose also Good for the Gander?: A Diagnostics Appraisal of the FIFA’s Proscription of Third Party Ownership of Professional Footballers’ Rights - Olowononi, Emmanuel Oluwafemi (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
This paper takes a critical analysis of football transfer market rules of third party Ownership of Professional Footballers’ Rights by appraising the Case of Carlos Tevez and Javier Mascherano and FIFA’s restrictive measures. The work examines the essential underpinning principles and philosophical justification of the proscription of the practice by FIFA. In doing this, the work considers the sophistication and extant development of the various football continental bodies. The work concludes that what is good for the goose is not always good for the gander and as such total proscription is unacceptable